2005
DOI: 10.1890/05-0377
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Intraspecific Diversity Enhances Settling Success in a Marine Invertebrate

Abstract: Theoretical and empirical research during the last decade suggests that increasing species richness often enhances ecosystem processes such as productivity, nutrient cycling, or resistance to disturbance. By analogous reasoning, it can be hypothesized that genetic diversity within species will have equivalent effects; however, this hypothesis has rarely been tested. We present experimental support for the positive effects of intraspecific diversity on a key trait: larval settlement in a marine invertebrate, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 36 publications
(39 reference statements)
6
75
2
4
Order By: Relevance
“…If C. gigas does display facilitative settling behaviour, this would further enhance the effect of greater colonisation with repeated, smaller, inoculations. Gregariousness between genetically distinct larval cohorts has also been shown to cause increased colonisation in marine invertebrates (Gamfeldt et al 2005), however variability was reduced in our study by using multiple adults from a common commercial breeding line with reduced genetic variability relative to wild populations.…”
Section: Facilitationmentioning
confidence: 92%
“…If C. gigas does display facilitative settling behaviour, this would further enhance the effect of greater colonisation with repeated, smaller, inoculations. Gregariousness between genetically distinct larval cohorts has also been shown to cause increased colonisation in marine invertebrates (Gamfeldt et al 2005), however variability was reduced in our study by using multiple adults from a common commercial breeding line with reduced genetic variability relative to wild populations.…”
Section: Facilitationmentioning
confidence: 92%
“…For example, decreased genetic variation in populations of barnacle larvae had a negative impact on larval recruitment (Gamfeldt et al 2005). In seagrass meadows, it has been shown that stands with less genetic variation are less productive, have lower diversity of associated flora and fauna, and are more susceptible toward extreme climate conditions (Reusch et al 2005).…”
Section: Effects Of Genetic Variation On Ecosystem Functionmentioning
confidence: 99%
“…Despite a growing interest among ecologists and conservation biologists in population-level consequences of phenotypic variation and polymorphism [3][4][5][6]10,[12][13][14], little experimental evidence is available to confirm that establishment success is higher for groups of dissimilar individuals [15,16], and the role of variation in functionally important phenotypic traits for establishment has never been examined under natural conditions in the wild. Tetrix subulata pygmy grasshoppers (Orthoptera: Tetrigidae) are well suited for such a study.…”
Section: Introductionmentioning
confidence: 99%